Echocardiographic effects of sodium-glucose cotransporter 2 inhibitors in single ventricle circulatory failure - Neijenhuis, Ralph M.L.; Regeer, Madelien V.; Walker, Niki L.; Hunter, Amanda; Kiès, Philippine; Holman, Eduard R.; Jukema, J. Wouter; Jongbloed, Monique R.M.; Veldtman, Gruschen R.; Egorova, Anastasia D. (International journal of cardiology congenital heart disease, 2025)
Single ventricle patients are at high risk of developing circulatory failure. There is limited evidence for pharmacological treatment. This study assessed the echocardiographic changes in ventricular function during sodium-glucose cotransporter 2 inhibitor (SGLT2i) therapy in patients with single ventricle failure (SVF). SVF patients with a baseline transthoracic echocardiogram within six months before starting SGLT2i and at least one echocardiographic examination within twelve months follow-up were included from a real-world international registry of adult congenital heart disease patients on SGLT2i. Mixed models were used to evaluate longitudinal changes in ventricular function and differences between patients with SVF with ≥ moderately reduced systolic function (SVFrEF) and with ≤ mildly reduced function (SVFpEF). Thirteen patients were included. The median age was 21 [20–42] years, 8 (61.5 %) were female, 10 (76.9 %) had a Fontan circulation, 8 (61.5 %) had SVFrEF, and 5 (38.5 %) SVFpEF at the start of SGLT2i. The mean follow-up was 7.6 ± 3.3 months. End-systolic area decreased significantly in all patients (−1.6 cm2 per month, p = 0.007) in the first 100 days. Fractional area change improved in the first 100 days in SVFrEF patients (3.5 %-point per month, p < 0.001), while SVFpEF patients remained stable. There was a significant improvement in the free wall strain in all patients (−0.3 %-point per month, p = 0.036) but not in global longitudinal strain (p = 0.087). Isovolumic acceleration also improved in the first 100 days (0.5 m/s2 per month, p = 0.010). Echocardiographic signals of improved ventricular function were observed in the first year of SGLT2i therapy in patients with SVF. [Display omitted] •The effects of SGLT2i in single ventricle failure (SVF) are unknown.•Mixed models were utilized for real-world repeated measurement analyses.•Although cautious, there are signs of improved ventricular function after SGLT2i.•SVF patients with reduced systolic function might benefit more from SGLT2i.•Future studies should evaluate SVF phenotype-specific responses to SGLT2i.